Виклики для управління продовольчими ресурсами в умовах війни - Павленко, Олена Сергіївна; Pavlenko, Оlena; Моголівець, О. А.; Moholivets, O. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2024)
В умовах війни управління продовольчими ресурсами стає одним із найважливіших завдань для забезпечення національної безпеки та підтримки життєздатності населення. Військові конфлікти призводять до масових руйнувань аграрної інфраструктури, порушення виробничих процесів і логістичних ланцюгів постачання продовольства. Це ускладнює доступ до продовольчих ресурсів, особливо в найбільш постраждалих регіонах та підвищує залежність від гуманітарної допомоги. Через нестабільність ситуації виникають значні коливання цін на продукти харчування,що посилює інфляційний тиск та обмежує купівельну спроможність населення. Урядові організації стикаються з проблемою забезпечення рівномірного розподілу наявних ресурсів та швидкого реагування на кризові ситуації. Для успішного подолання цих викликів потрібен комплексний підхід, який включає активну співпрацю між державою, приватним сектором, міжнародними організаціями та місцевими громадами. Пріоритетним є впровадження сучасних цифрових технологій та систем моніторингу, що дозволить відстежувати ситуацію в режимі реального часу та оперативно коригувати плани дій. Управління запасами продовольства, координація гуманітарної допомоги, підтримка аграрного сектору та відновлення інфраструктури — ключові заходи, які можуть допомогти зменшити негативний вплив війни на продовольчу безпеку. Водночас необхідно розробити стратегії резервування ресурсів та підвищення стійкості продовольчих систем, що стане основою для відновлення та подальшого розвитку сільського господарства у повоєнний період. Managing food resources during wartime is a complex challenge that impacts national security, economic stability, and public health. War leads to the destruction of agricultural infrastructure, reduced production, logistical disruptions, and inflationary pressures in food markets. The decline in production due to damage to farms, irrigation systems, and transport networks results in food shortages and price surges. Farmlands become unusable due to contamination by mines and unexploded ordnance, while the lack of water for irrigation exacerbates the situation. The displacement of agricultural workers and scarcity of resources such as seeds and fertilizers further reduce production volumes, intensifying the food crisis. Logistical challenges in wartime present another significant obstacle. Destroyed transportation routes and the inherent dangers of transporting goods through conflict zones make market access difficult. This disruption hampers the delivery of locally produced food to urban centers and conflict-affected regions where it is most needed. It also makes food imports more complex and costly, putting additional pressure on national food reserves. Supply chain breakdowns contribute to market volatility, resulting in fluctuating food prices that disproportionately impact vulnerable populations, including the poor and displaced. Wartime conditions often lead to inflationary pressures, exacerbating economic instability. Reduced food production combined with supply chain disruptions creates scarcity, driving up prices and making basic food items unaffordable. Additionally, governments under wartime economic pressures might implement restrictive policies like price controls or export bans to stabilize domestic markets. However, these measures can have unintended consequences, such as fostering black-market activities, discouraging agricultural investments, and distorting food supply chains further. Nations dependent on food imports face increased vulnerability to global market shocks, as war-induced supply issues intensify competition for scarce food resources internationally. Effective management of food resources during wartime requires coordinated strategies that address both immediate and long-term needs. This includes establishing food reserves, protecting critical agricultural infrastructure, and creating contingency plans for food distribution. Governments can support farmers by providing subsidies for essential inputs, such as seeds and fertilizers, to sustain agricultural production during conflicts. Investment in resilient food systems, such as alternative supply routes and enhanced storage facilities, is crucial. Digital technologies and real-time monitoring systems can provide data on crop yields, market prices, and conflict developments, enabling more responsive and flexible resource management.
Challenges for managing food resources in wartime conditions
Keywords: продовольча безпека; food security; аграрна інфраструктура; agricultural infrastructure; логістика продовольства; food logistics; продовольча криза; food crisis; управління ресурсами; resource management